Comparison of Axillary Drain Output After Level 2 Dissection Using Monopolar Electrocautery Versus LigaSure - Farkhanda Niaz; Muhammad Umair Afzal; Rashid Iqbal; Adnan Ahmed Raza; Rabbia Abdul Ghani; Abrar Ahmad (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Conventional monopolar electrocautery in level-II axillary lymph-node dissection is associated with seroma formation and thermal injury. LigaSure, an electrothermal bipolar vessel-sealing system, may reduce postoperative drainage. The study aimed to compare axillary drain output after level II dissection using electrocautery vs. Ligasure.